A systematic review of language learner strategy research in the face of self-regulation. (February 2018) - Rose, Heath; Briggs, Jessica G.; Boggs, Jill A.; Sergio, Lia; Ivanova-Slavianskaia, Natalia
Abstract: Language learner strategy research has been dogged by criticisms in recent decades culminating in calls for the field to be replaced with the construct of self-regulation. This paper aims to evaluate how the field has responded to such critique, and to investigate how self-regulation has impacted strategy research in recent years. The study utilizes a systematic review methodology to examine key studies conducted and published from 2010 to 2016 to reveal current trends, and to elucidate best research practices. After initially searching more than 1000 research papers, 46 of the most field-aware studies were selected for data extraction, of which 24 were included in a final systematic map for analysis. Results show strategy research is highly reliant on quantitative measures of data collection, but also reveal a number of context-situated qualitative methods which have produced valuable results. An in-depth review of the 15 most relevant studies revealed a number of innovations that have considerably advanced language learning strategy research in recent years. In a field awash with studies that are anchored to past methodologies, this paper showcases state-of-the-art work in the field, with an aim to inform future research.